A review of the genus Atrovirensis Kononenko, 2001 with description of four new species from China (Lepidoptera, Noctuidae: Xyleninae, Apameini) - Han, H.l.; Pan, Z.h.; Kononenko, V.s. (Zootaxa, 2016)
The genus Atrovirensis Kononenko, 2001 is reviewed. Four new species (Atrovirensis parannamita sp. n., Atrovirensis furcatus sp. n., Atrovirensis sacculatus sp. n. and Atrovirensis miraculosus sp. n.) are described from China. A new combination Atrovirensis euplexina (Draudt, 1950), comb. n. [Valeria] is proposed. Two taxa of uncertain status (Atrovirensis sp. cf. parannamita and Atrovirensis sp. cf. furcatus) are included to the review. The updated checklist of the genus is presented. All taxa of the genus Atrovirensis are illustrated in colour with black and white photographs of their genitalia in 48 figures.